Polyphenols and IUGR Pregnancies: Effects of the Antioxidant Hydroxytyrosol on Brain Neurochemistry and Development in a Porcine Model - Yeste, Natalia (Antioxidants (Basel), 2021)
Supplementation of a mother’s diet with antioxidants, such as hydroxytyrosol (HTX), has been proposed to ameliorate the adverse phenotypes of fetuses at risk of intrauterine growth restriction. In the present study, sows were treated daily with or without 1.5 mg of HTX per kilogram of feed from day 35 of pregnancy (at 30% of total gestational period), and individuals were sampled at three different ages: 100-day-old fetuses and 1-month- and 6-month-old piglets. After euthanasia, the brain was removed and the hippocampus, amygdala, and prefrontal cortex were dissected. The profile of the catecholaminergic and serotoninergic neurotransmitters (NTs) was characterized and an immunohistochemical study of the hippocampus was performed. The results indicated that maternal supplementation with HTX during pregnancy affected the NT profile in a brain-area-dependant mode and it modified the process of neuron differentiation in the hippocampal CA1 and GD areas, indicating that cell differentiation occurred more rapidly in the HTX group. These effects were specific to the fetal period, concomitantly with HTX maternal supplementation, since no major differences remained between the control and treated groups in 1-month- and 6-month-old pigs.